2016
DOI: 10.1242/jcs.188185
|View full text |Cite
|
Sign up to set email alerts
|

ZO-1 interactions with F-actin and occludin direct epithelial polarization and single lumen specification in 3D culture

Abstract: Epithelia within tubular organs form and expand lumens. Failure of these processes can result in serious developmental anomalies. Although tight junction assembly is crucial to epithelial polarization, the contribution of specific tight junction proteins to lumenogenesis is undefined. Here, we show that ZO-1 (also known as TJP1) is necessary for the formation of single lumens. Epithelia lacking this tight junction scaffolding protein form cysts with multiple lumens and are defective in the earliest phases of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
94
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(114 citation statements)
references
References 77 publications
12
94
2
Order By: Relevance
“…This was followed by a series of studies indicating critical roles for occludin and included reports that occludin overexpression could drive formation of intracellular multilamellar bodies with closely apposed lipid bilayers, similar to those in tight junctions (Furuse et al 1996), and that occludin both enhanced steady-state barrier function in cultured monolayers and increased the number of strands seen by freeze-fracture electron microscopy (McCarthy et al 1996). Occludin functions appear to require the cytoplasmic C terminus (Chen et al 1997; Matter and Balda 1999; Odenwald et al 2016), which is heavily phosphorylated in tight junction-associated occludin (Cordenonsi et al 1997; Sakakibara et al 1997; Wong 1997) and binds to ZO-1, ZO-2, and ZO-3 (Itoh et al 1999). Further, introduction of a synthetic peptide corresponding to part of occludin’s second extracellular loop (ECL2) disrupted epithelial paracellular barrier function (Wong and Gumbiner 1997).…”
Section: Tight Junction Molecular Architecturementioning
confidence: 99%
“…This was followed by a series of studies indicating critical roles for occludin and included reports that occludin overexpression could drive formation of intracellular multilamellar bodies with closely apposed lipid bilayers, similar to those in tight junctions (Furuse et al 1996), and that occludin both enhanced steady-state barrier function in cultured monolayers and increased the number of strands seen by freeze-fracture electron microscopy (McCarthy et al 1996). Occludin functions appear to require the cytoplasmic C terminus (Chen et al 1997; Matter and Balda 1999; Odenwald et al 2016), which is heavily phosphorylated in tight junction-associated occludin (Cordenonsi et al 1997; Sakakibara et al 1997; Wong 1997) and binds to ZO-1, ZO-2, and ZO-3 (Itoh et al 1999). Further, introduction of a synthetic peptide corresponding to part of occludin’s second extracellular loop (ECL2) disrupted epithelial paracellular barrier function (Wong and Gumbiner 1997).…”
Section: Tight Junction Molecular Architecturementioning
confidence: 99%
“…1B). Subsequent immunostaining of these clusters revealed proper localization of Factin to apical membranes, and E-cadherin to lateral cell-cell contacts -hallmarks of epithelial polarization (23). These spheroids formed when the hydrogel was adhered to an underlying substrate.…”
Section: Resultsmentioning
confidence: 99%
“…ALIX was shown to maintain the epithelial blood–cerebrospinal fluid barrier by facilitating assembly of tight junctions (Campos et al , ), which were recently reported to control spindle orientation in Caco‐2 cyst cells (Odenwald et al , ). In general, cell–cell contacts such as tight junctions seem to control MS orientation in epithelial cells by F‐actin, an essential component of the cell cortex facilitating capture of astral MTs (di Pietro et al , ; Tuncay & Ebnet, ).…”
Section: Discussionmentioning
confidence: 99%